2018
DOI: 10.1002/jcp.27098
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields promote bone formation by activating the sAC–cAMP–PKA–CREB signaling pathway

Abstract: The application of pulsed electromagnetic fields (PEMFs) in the prevention and treatment of osteoporosis has long been an area of interest. However, the clinical application of PEMFs remains limited because of the poor understanding of the PEMF action mechanism. Here, we report that PEMFs promote bone formation by activating soluble adenylyl cyclase (sAC), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and cAMP response element-binding protein (CREB) signaling pathways. First, it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
(83 reference statements)
1
37
0
Order By: Relevance
“…The solenoid was 27 cm long and 14 cm in diameter, in which EMF signals of high uniformity could be generated, thus ensuring all cells were subjected to the same intensity of EMFs . The EMF generator used to treat the experimental rats was based on our same patent, and could provide a homogenous range of EMFs in which all rats were exposed to same EMFs in a cage . The EMFs, including static magnetic fields, continuous (sinusoidal, triangular, and square waveforms), and PEMFs, could be produced within the range of frequencies at 5 to 100 Hz and intensities at 0.0 to 5.0 mT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solenoid was 27 cm long and 14 cm in diameter, in which EMF signals of high uniformity could be generated, thus ensuring all cells were subjected to the same intensity of EMFs . The EMF generator used to treat the experimental rats was based on our same patent, and could provide a homogenous range of EMFs in which all rats were exposed to same EMFs in a cage . The EMFs, including static magnetic fields, continuous (sinusoidal, triangular, and square waveforms), and PEMFs, could be produced within the range of frequencies at 5 to 100 Hz and intensities at 0.0 to 5.0 mT.…”
Section: Methodsmentioning
confidence: 99%
“…(18) The EMF generator used to treat the experimental rats was based on our same patent, and could provide a homogenous range of EMFs in which all rats were exposed to same EMFs in a cage. (20) The EMFs, including static magnetic fields, continuous (sinusoidal, triangular, and square waveforms), and PEMFs, could be produced within the range of frequencies at 5 to 100 Hz and intensities at 0.0 to 5.0 mT. The generator was calibrated by the staff at the Department of Magnetic Fields at the Institute of Modern Physics in Lanzhou, China.…”
Section: Emf Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have shown that cAMP signaling is localized in the primary cilium and plays a role in the dynamic modulation of ciliary length (Besschetnova et al, 2010). Blocking cAMP signaling with adenylate cyclase or PKA inhibitors abolished the osteogenic effect of PEMFs Wang, Li, et al, 2018;Wang, Pu, et al, 2018). In addition, phosphorylated PKA was also found to localize in the primary cilium; this protein is preferentially localized to the entire cilium and sometimes to the ciliary base and/or tip in osteoblasts Shi, Xie, et al, 2017).…”
Section: The Primary Cilium As An Electromagnetic Field Sensormentioning
confidence: 92%
“…PEMFs activate cAMP/PKA/CREB signaling by increasing intracellular cAMP levels, facilitating the phosphorylation of PKA and CREB, and inducing the nuclear translocation of phosphorylated CREB both in vitro and in vivo. Blocking cAMP signaling with adenylate cyclase or PKA inhibitors abolished the osteogenic effect of PEMFs Wang, Li, et al, 2018;Wang, Pu, et al, 2018).…”
Section: Interconnection Of the Primary Cilium And The Cytoskeletonmentioning
confidence: 99%